The New Law of Squeeze-Out Mergers - Marc I. Steinberg; Evalyn N. Lindahl (Washington University Law Quarterly, 1984)
In response to the United States Supreme Court's decision in Santa Fe Industries, Inc. v. Green, which sharply limited the role of federal securities law in redressing acts of corporate malfeasance, the Delaware Supreme Court, in Singer v. Magnavox Co. and its progeny, expanded the protection available to investors in the context of squeeze-out mergers. According to some proponents of corporate accountability, however, the Delaware Supreme Court's decision in Weinberger v. UOP, Inc. indicates a return to the "race for the bottom" in state corporate law. The Weinberger decision limited the scope of protection available to minority shareholders under Delaware law. Significantly, in order to obtain relief in most instances, minority stockholders are required to perfect their rights under the cumbersome procedural requirements of the Delaware appraisal statute. After canvassing Delaware law prior to Weinberger, the Article addresses the implications of this important decision. Weinberger’s application of the "entire fairness" test as the sole standard to scrutinize squeeze-out mergers raises a number of intriguing issues, which the Article examines. In addition, significant developments in other jurisdictions are discussed where appropriate. Thereafter, the Article analyzes the role of the investment banker in rendering a fairness opinion pursuant to a freeze-out merger, focusing on the fiduciary duties an investment banker may owe to minority shareholders when the banker is appraising the value of the minority's interest. The last section of the Article discusses Weinberger’s impact on the federal securities laws, and in particular, SEC rules 13e-3 and l0b-5.
Keywords: Consolidation & merger of corporations; Weinberger v. UOP; Inc. 457 A.2d 701 (Del. 1983); Disclosure (Securities law); Fiduciary duties; Insider trading (Securities); Securities Exchange Act; Delaware